The Relation between the Number of Hours That Authorize the Sale of Alcoholic Beverages and Violence - Carlos Huaco; Marco Gonzalez; Hernán Malaga; Manuel Sotelo (Tabriz University of Medical Sciences, 2012)
Background: La Victoria was considered, the most violent area in Lima City, the local governmentenforced a public policy regarding number of hours for selling of alcoholic beverages inJanuary 2007. The study was designed to compare its results in Violence between one districtwith the law and other without the law.Methods: This retrospective cross-sectional was an ecological study with a chronological andgeographical comparison between La Victoria, with the restriction and Cercado de Lima withoutthe ban. The participants in the study were patients from a local National Hospital, with aggressionsfrom fighting, or were wounded in traffic accidents, and violent death bodies at NationalInstitute of Legal Medicine. Data were analyzed, using clinical histories (2006 vs. 2007-8) and necropsies(2005-6 vs. 2007-8)Results: The reduction of aggression rates at La Victoria in 2007 and 2008 in comparison to2006, were 40.7% and 36.4% respectively (P< 0.05). It was related to the number of hours of liquorauthorized selling Y= -11.25+27.32 X (P<0.05). There was a reduction of 44% in homicide(P<0.05) and 35% in suicide rates between biennia's. The female/ male ratio of homicideschanged from 1/7.3 to 1/4.6. A significant increase in the rate of alcohol positive dead bodieswas observed (20.3% to 41.5%), (Relative Risk (RR) = 2.03, (95% Confidence Interval (CI) =(1.09-3.8), χ²(1)=5.24, ( P< 0.05).Conclusions: The reduction of violence was probably due to the ban, indicating the importanceof programs to control alcohol consumption which lead to decrease the rate of violence and its'consequences like homicides, impulsive violence.